A Confirmed Case of Idiopathic Pulmonary Fibrosis - Probable Usual Interstitial Pneumonia Pattern through Lung Biopsy - Kristiani, Maria; Djajalaksana, Susanthy; Erawati, Dini; Yudhanto, Hendy; Bayuadi, Imam (Universitaas Brawijaya, 2022)
Background: Although classified as a rare disease, the global burden of disease study reports showed that interstitial lung disease is ranked 40th in the diseases with high mortality, and its prevalence had increased by 86% since 1990. The most common interstitial lung disease”idiopathic pulmonary fibrosis (IPF)”has low survival rates”2-3 years after diagnosis”and is irreversible. Establishing a definite diagnosis of IPF is very difficult because it needs a multidisciplinary approach, as an establishment based on the description of HRCT and lung biopsy is needed. The goal of therapy is to prevent the progression of fibrosis. Case: We report a case of an adult woman, 46 years old with idiopathic pulmonary fibrosis (IPF) with Probable Usual Interstitial Pneumonia (UIP) pattern at dr. Saiful Anwar Hospital. History taking, physical examination and laboratory and chest Xray examination of the patient found a suspicion of ILD. CT-scan showed fibrosis in both lungs, honeycomb appearance with pulmonary bronchiectasis traction, which fit the description of IPF, and thus suspended the diagnosis of ILD. VATS pulmonary biopsy confirmed the diagnosis of IPF. The patient experienced a decrease in clinical conditions, as her complaint was worsening in the last month, in accordance to the state of acute exacerbations. Conclusion: In this patient, the diagnosis of IPF with Probable UIP pattern was made through a multidisciplinary approach, including the pulmonology, radiology and anatomical pathology department. Keywords: IPF, IPF, Probable UIP Pattern, IPF Diagnosis